2020
DOI: 10.1080/16078454.2020.1859249
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous missense mutation (Met527Ile) in a consanguineous marriage family with inherited factor XII deficiency

Abstract: Objective: To identify potential mutations of the FXII gene (F12) in a consanguineous marriage family with hereditary coagulation factor XII (FXII) deficiency, and it will improve the understanding of the pathogenesis involved in the disease. Clinical presentation: The proband was a 58-year-old male who had chronic gastritis. He was found to have a significantly prolonged activated partial thromboplastin time (APTT) at 101.0s (reference range, 29.0-43.0 s) before stomachendoscopy. Techniques: The coagulation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…10 Congenital FXII deficiency can be divided into two types: The cross-reacting material-negative group (CRM À ) is characterized by synchronously decreased FXII:C and FXII:Ag, whereas CRM-positive group (CRM þ ) has the feature of decreased activity but borderline-normal or normal antigen. 11 In this study, the FXII:C and FXII:Ag of the patient were significantly reduced simultaneously. Genetic analysis showed that the patient had a c.1748T > A homozygous missense mutation in exon 14 of the F12 gene, which led to the replacement of isoleucine (ATC) with asparagine (AAC) at amino acid position 583 (p.Ile583Asn).…”
Section: Discussionsupporting
confidence: 47%
“…10 Congenital FXII deficiency can be divided into two types: The cross-reacting material-negative group (CRM À ) is characterized by synchronously decreased FXII:C and FXII:Ag, whereas CRM-positive group (CRM þ ) has the feature of decreased activity but borderline-normal or normal antigen. 11 In this study, the FXII:C and FXII:Ag of the patient were significantly reduced simultaneously. Genetic analysis showed that the patient had a c.1748T > A homozygous missense mutation in exon 14 of the F12 gene, which led to the replacement of isoleucine (ATC) with asparagine (AAC) at amino acid position 583 (p.Ile583Asn).…”
Section: Discussionsupporting
confidence: 47%
“…Patients exhibit prolonged activated partial thromboplastin time (aPTT) in vitro, but there is no significant predisposition to bleeding as expected. Most cases are typically identified incidentally during routine health checks or preoperative coagulation screening tests [ 1 , 2 ]. This report describes two Chinese patients with FXII deficiency, neither of whom had significant abnormal bleeding symptoms as expected.…”
mentioning
confidence: 99%